Dreams come true, Norfatihah Mazuki receives Postgraduate Research Award - Siti Nurfarmy, Ibrahim (UMPSA, 2024)
GAMBANG, 26 October 2024 – Coming from a humble background fuelled the spirit and motivation for Norfatihah Mazuki, 29, to pursue her studies up to the Doctor of Philosophy (PhD) level at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).